TWO STAY TWO STRAY COOPERATIVE LEARNING MODEL IN MATHEMATICS LEARNING OUTCOMES - Monif Maulana (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2017)
The population in this study was seventh grade students consisting of 7 calsses. The sampling technique use random sampling technique that was by lottery class. From raffle earned that grade VII G class as TS-TS class and VII F Class as ekspository class. Mathematics learning outcomes data obtained using the test method in the form of objective questions. Analysis of the data used one tailed t-test and two tailed t-test. From the test results obtained by the two tailed t-test  = 1,9180 and  = 1,5409, it means  >  with a significance level of 5% and 54 degrees of freedom, which means  was rejected. This suggest that there were differences in mathematics achievement between students who use cooperative model of TS-TS and ekspository learning model. One tailed t-test result obtained that  = 1,9180 and  = 1,5409, it means  >  with a significance level of 5% and 54 degrees of freedom, which means  was rejected. This suggest that the learning outcomes of students who use the cooperative model of TS-TS was better than learning outcomes of students who use the ekspository learning model in even semester of seventh grade student in SMP Muhammadiyah 7 Yogyakarta academic year of 2016/2017